Does women's empowerment increase accessibility to healthcare among women facing domestic violence?. Issue 8 (16th November 2016) - Mahapatro, Meerambika
ABSTRACT: This article aims to understand whether women's empowerment increases access to healthcare among women facing domestic violence within the Indian context. It reports on a multi-centre cross-sectional study covering 18 states of India, with 14, 405 women respondents through a systematic multi-stage sampling strategy. Both quantitative and qualitative methods were used. Despite substantive possession of the existing attributes of empowerment, women fail to receive necessary healthcare services. This reflects a situation of biased policy processes and institutional frameworks, which are a manifestation of existing patriarchal norms and which result in the piecemeal processes of entitlements.